ANALISIS STRATEGI PEMASARAN PRODUK AR-RUM HAJI PADA PT. PEGADAIAN SYARIAH PASAR SEKETENG SUMBAWA BESAR - Marisa Sutanty; Razi Apriansyah Mustaram; K Kurniawansyah; Devi Armada; K Kamaruddin (Pusat Riset dan Publikasi, 2020)
This study aims to determine the marketing strategy on Haji Arrum product at PT. Pegadaian Syariah Seketeng, Sumbawa Besar. This is a descriptive study conducted to determine the value of the independent variable. The data used in this study is qualitative in the form of the informants' descriptions related to the study object. The data obtained directly from the data source through interviews. There were 13 informants in this study such as the manager, employee, sales promotion of PT. Pegadaian Syariah Seketeng, and 10 customers of Haji Arrum. The data analysis method carried out using the SWOT analysis technique. The results showed that the internal condition is the strength of UPS Pasar Seketeng which is that the Pegadaian Syariah is the only one outlet in Sumbawa Besar, but the lack of knowledge of employees regarding the Hajj Arrum products is weakness. Thus, they have difficulties in marketing. Meanwhile, the external condition such as the Sumbawa regency which is a majority of Muslim supports the Haji Arrum marketing. But, there are unfortunate situations such as the emergence of competitors which sell a similar product. An alternative strategy is maximizing the marketing strategies and also expanding the market share by opening branches/ outlets around Sumbawa and other areas to increase promotion and to reach customers easier.